Mapeamento geológico-geotécnico do núcleo urbano central do município de Ilhabela - SP - Diniz, Tales de Deus [UNESP] (2015)
The urbanization process in Brazil occurs mainly in a non-ordered way, not considering properly the potentials and limitations of the physical environment, what results in a form of urban development that may expose the population and the urban equipment to external geological processes such as floods and mass movements. It happens in Ilhabela-SP, where the high rates of population growth, combined with its rough topography, increase this issue, highlighting the need of an adequate orientation to the urban expansion. In this context, the geological-geotechnical maps happen to be appropriate tools for the planning of the urban expansion in the physical environment. So the aim of this research is the geological-geotechnical mapping of the most densely urbanized area of Ilhabela, through the integrated analysis of the region's aerial images. The photo analysis and photo interpretation, combined with field data, subsidized the section and classification of the study area in geological-geotechnical units that show similar morphological and geotechnical properties. This procedure resulted in the identification of geological-geotechnical units, which were represented in 3 scales, each with a different level of details (1:50.000, 1:20.000, 1:10.000), and accompanied of profiles and description tables containing its physical and land use characteristics and main acting processes, besides the representation of its alteration profile and characteristic relief. The products obtained allowed a wide ranged comprehension of the island's physical environment characteristics, as well as the main conditioning aspects of it's human occupation, so happening to be useful tools that are appropriate to the urban planning of the archipelago city